The law of security and title-based financing - Beale, H. G.; Bridge, M. G.; Gullifer, Louise; Lomnicka, Eva Z. (Oxford : Oxford University Press, 2018)
The first edition was titled ''the law of personal property security''. the second edition was under the current title ''the law of security and title -based finance''. the book covers all forms of property except land despite the omission of the word personal property in the new title. the book makes a genuine attempt to cover both security and quasi-security.
Rev. ed. of: The law of personal property security. [1st ed.]. 2007.
Includes bibliographical references and index.
nmn 08/01/2019
Loans
Keywords: Security (Law); Personal property; Debtor and creditor; Great Britain